2002
DOI: 10.1002/gcc.10049
|View full text |Cite
|
Sign up to set email alerts
|

The position of pulmonary carcinoids within the spectrum of neuroendocrine tumors of the lung and other tissues

Abstract: Bronchopulmonary carcinoids comprise 25% of all human carcinoids. The World Health Organization divides them into typical (TC) and atypical forms (ATC), distinguished by differences in mitotic counts lower or higher than 2/2 mm(2) and the presence or absence of necrosis. The reproducibility of this classification with respect to the borderline cases with 1-2 mitotic counts/2 mm(2) has been questioned. We have analyzed 15 TCs and 20 ATCs by comparative genomic hybridization. Loss of 11q was the most frequent ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 26 publications
3
42
2
1
Order By: Relevance
“…These results are in keeping with previous observations of a progressive accumulation of genetic defects from low-to high-grade neuroendocrine lung neoplasms. 8,9 Although a transition of either typical or atypical carcinoids to high-grade neuroendocrine carcinomas is currently deemed to be unlikely, 10 we herein indicate that carcinoids and large cell neuroendocrine carcinomas may share common genetic alterations on X chromosome, suggesting a critical role for these chromosomal regions in the pathogenesis of both tumors. Moreover, the finding of several X chromosome LOH in large cell neuroendocrine carcinomas but not in small cell lung carcinomas supports the view that these highly aggressive lung neuroendocrine carcinomas are genetically different.…”
Section: Discussionmentioning
confidence: 62%
“…These results are in keeping with previous observations of a progressive accumulation of genetic defects from low-to high-grade neuroendocrine lung neoplasms. 8,9 Although a transition of either typical or atypical carcinoids to high-grade neuroendocrine carcinomas is currently deemed to be unlikely, 10 we herein indicate that carcinoids and large cell neuroendocrine carcinomas may share common genetic alterations on X chromosome, suggesting a critical role for these chromosomal regions in the pathogenesis of both tumors. Moreover, the finding of several X chromosome LOH in large cell neuroendocrine carcinomas but not in small cell lung carcinomas supports the view that these highly aggressive lung neuroendocrine carcinomas are genetically different.…”
Section: Discussionmentioning
confidence: 62%
“…Using conventional CGH techniques, comparative analyses of the genomic differences among SCLC, bronchial carcinoids, and GI carcinoids have been conducted (41)(42)(43). Through comparison of bronchial carcinoids and SCLCs, Ullmann et al (41) found that carcinoids carried fewer chromosomal aberrancies than SCLC tumors and that SCLC tumors were characterized by many gains and losses in their genome.…”
Section: Discussionmentioning
confidence: 99%
“…In pulmonary carcinoids, an interesting subset of endocrine tumors, similar MEN1 alterations have been reported and considered to be involved in the development of these tumors (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 68%
“…Alterations of the MEN1 gene occur in a great variety of endocrine tumors and they are considered also to be involved in the pathogenesis of pulmonary carcinoids (17)(18)(19)(20)(21)(22)(23)(24). Specifically, allelic deletions and mutations of the MEN1 gene have been reported in lung carcinoid tumors, including those developing sporadically in the absence of MEN1 syndrome (17,20,24).…”
Section: Discussionmentioning
confidence: 99%